Advances in the MYB–bHLH–WD Repeat (MBW) Pigment Regulatory Model: Addition of a WRKY Factor and Co-option of an Anthocyanin MYB for Betalain Regulation - Alan Lloyd; Austen Brockman; Lyndsey Aguirre; Annabelle Campbell; Alex Bean; Araceli Cantero; Antonio González (2017)
Flavonoids are secondary metabolites derived from the general phenylpropanoid pathway and are widespread throughout the plant kingdom. The functions of flavonoids are diverse, including defense against phytopathogens, protection against UV light damage and oxidative stress, regulation of auxin transport and allelopathy. One of the most conspicuous functions of flavonoids has long attracted the attention of pollinators and scientist alike: the vivid shades of red, pink, orange, blue and purple on display in the flowers of angiosperms. Thus, flavonoid pigments have perhaps been the most intensely studied phenylpropanoids. From Mendel to McClintock and up to the present, studies centered on flavonoid pigments have resulted in some of the most important scientific discoveries of the last 150 years, including the first examples of transcriptional regulation in plants. Here we focus on the highly conserved MYB–bHLH–WD repeat (MBW) transcriptional complex model for the regulation of the flavonoid pigment pathway. We will survey the history of the MBW model spanning the last three decades, highlighting the major findings that have contributed to our current understanding. In particular, recent discoveries regarding WRKY protein control of the flavonoid pigment pathway and its relationship to the MBW complex will be emphasized. In addition, we will discuss recent findings about the regulation of the beet betalain pigment pathway, and how a MYB member of the MBW complex was co-opted to regulate this chemically unrelated but functionally equivalent pathway.